The Golod Property on Monomial Rings - Gilbert, Cody (Wake Forest University, 2018)
In this paper, we work towards understanding a counterexample found in Lukas Katthan's "A non-Golod Ring with a Trivial Product on its Koszul Homology". In this counterexample, Katthan disproved a claim made by Berglund and Jollenbeck which stated that a monomial ring is Golod if and only if the product on its Koszul Homology is trivial. At the end, we find a non-Golod monomial ring with trivial product on its Koszul homology, so we will need the backwards direction to be stronger in order for this statement to be true.
Keywords: Algebraic Topology; Commutative Algebra; Homological Algebra